Profitability of Listed Pharmaceutical Companies in Bangladesh: An Inter & Intra Comparison AMBEE & IBN SINA Companies Ltd - Nimalathasan, B. (Analele of University Bucharest, 2009)
The pharmaceutical market of Bangladesh very much dynamic and competitive and is comparable to those of developed countries. It is a matter of great pleasure that this sector successfully fulfils major portion of local demand of pharmaceutical products and at the same time it is moving forward to explore the international market for chemicals and pharmaceuticals products. The contribution of pharmaceuticals companies in Bangladesh to the national economy is encouraging. The investment in this sector is increasing which speaks about the potentiality in this sector. This sector satisfies the demand of the local market and also goes for export to explore the international market. Presently these industries exporting medicines to more than 50 countries of the world. Hence, the present study is initiated Profitability of Listed pharmaceuticals Companies: An Inter and Intra Comparison of Ambee and Ibn Sina pharmaceuticals companies in Bangladesh with three (03) years accounting period from 2005-2007. The study reveals that, AMBEE Pharmaceuticals Ltd (AMBPH) should be considered as satisfactory its indicators of profitability higher than the industry average, except average operating profit ratio and average net profit ratio. On the other hand IBN SINA Pharmaceuticals Ltd (IBN SINAPH), it has not been able to attain the industry average gross profit, operating profit, return on investment, return on capital employed and return on equity. But it has succeeded to attain the standard norm for these ratios. Therefore its profitability may be considered to some extent satisfactory. It can be concluded that the profitability of pharmaceutical companies is very much satisfactory as both of the companies according to the standard norms of profitability in terms of investment.
Keywords: Profit; Profitability; Pharmaceuticals industry